Intervening role of loyalty reward programs and E-word-of-mouth on smartphone brand loyalty in Malaysia - Mohammadi, Alireza (2019)
In this research, brand loyalty is assessed under specific boundaries created by social media marketing factors and Electronic Word of Mouth (eWOM). The objective of the present research is to determine the significance of the relationship between social media marketing factors including social network advertising, social media brand communities, and loyalty reward programs with brand loyalty in smartphone market in Malaysia. This investigation examines the mediating influence of loyalty reward programs and moderating role of eWOM on brand loyalty in smartphone market of Malaysia. The Theory of Planned Behavior, Theory of Social Identity, and Laroche model of effects of the brand communityare used to develop the research framework. This study successfully designed and developed a model which improves the present perception of brand loyalty in the smartphone market using the quantitative research approach. The questionnaire is designed and the evaluation is based on the five-point Likert scales. Throughout the time frame allocated, a total of 690 useful responses from individuals who own at least one smartphone, living in Malaysia were gathered. The respondents are selected using a simple random sampling technique through online questionnaire distributed in social media and social network platforms. The collected ordinal data are further analyzed statistically using the PLS-SEM, a nonparametric analysis approach to determine the relationships and path coefficients between the proposed variables. This study demonstrates the significance of the relationship between social network advertising, social media brand communities, loyalty reward programs and eWOM with brand loyalty in the smartphone market of Malaysia. Furthermore, the results of this research demonstrate that loyalty reward programs mediate the relationship between social network advertising and social media brand communities with brand loyalty in the Malaysian smartphone market. This study verifies the moderating role of eWOM on the relationship between loyalty reward programs and brand loyalty. The findings of this research benefit both academia and the smartphone industry. The results enhance the theoretical understanding of brand loyalty, customer loyalty, brand switch behavior, social media marketing factor, and eWOM. Finally, the findings of this study provide significant insights for smartphone manufacturers on how they can improve the brand loyalty status among their patrons through social media marketing factors and eWOM.